Increasing of antioxidant and superoxide dismutase activity in chicory transgenic plants - Kvasko, O.Yu.; Matvieieva, N.A. (Вiopolymers and Cell, 2013)
Aim. Determination of the antioxidant activity (AOA) and superoxide dismutase (SOD) activity in transgenic chicory plants carrying the human interferon α2b target and nptII or bar selective genes. Methods. AOA was measured by a method based on the determination of kinetics of the reduced 2,6-dichlorophenolindophenol oxidation. SOD activity was assayed using the system consisting of ethionine, riboflavin, and nitroblue tetrazolium. Results. Antioxidant activity of transformed plants extracts was more than 1,91–2,59 and 2,04–2,43 times over the activity of control non-transgenic plants (at nptII and bar gene presence respectively). SOD activity was higher in transgenic plants than in the control, and was 2,03 ± 0,46–3,33 ± 0,54 U/g weight (nptII gene) and 2,25 ± 0,46–2,68 ± 0,08 U/g weight (bar gene). Conclusions. Transgenic C. intybus plants have higher antioxidant and superoxide dismutase activity compared to non-transgenic plants. The increasing of AOA and SOD activity is a response of plants to transformation stress factor and integration of foreign genes in plant genome.